Peningkatan Persepsi Gizi pada Remaja dalam Upaya Pencegahan Kejadian Anemia - Permata, Reni; Untari, Untari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Anemia is a medical condition in which the number of red blood cells or hemoglobin is less than normal. Normal hemoglobin levels are generally different in men and women. For men anemia is usually defined as a hemoglobin level of less than 13.5 grams/100 ml. Anemia is a common blood disorder that occurs when the level of red blood cells (erythrocytes) in the body becomes too low. This can cause health problems, because red blood cells contain hemoglobin, which carries oxygen to body tissues. Anemia can cause various complications including fatigue and stress on the body's organs. Anemia occurs due to lack of iron and folic acid in the body. Women who suffer from anemia will have an impact on pregnancy and have the potential to give birth to babies with low birth weight. Besides that, Anemia can result in the death of both mother and baby during childbirth. This community service aims to provide knowledge about the importance of consuming a variety of foods that contain iron. The implementation procedure is carried out by counseling youth about the importance of nutrition in preventing anemia, so that the problem of anemia in Indonesia can be resolved. The solution to the problem is to teach teenagers about the importance of knowing balanced nutrition and the importance of consuming iron, so it is hoped that adolescents do not experience anemia. The expected achievement target is that teenagers understand and know how to prevent the nutritional problem of anemia.